Cost-Effectiveness in Patients Undergoing Revascularization of Chronic Total Occluded Coronary Arteries—A Cohort Study - Holck, Emil Nielsen; Winther, Naja Stausholm; Mogensen, Lone Juul Hune; Christiansen, Evald Høj (Frontiers in Cardiovascular Medicine, 2022)
Background: Revascularization of patients with chronic total occluded coronary arteries (CTO) is recommended if they have symptoms despite medical treatment. Cost-effectiveness of treatment with percutaneous coronary intervention (PCI) was investigated in this cohort study. Methods and materials: The study was designed as a cohort study enrolling all patients undergoing PCI for a CTO in the Central Region of Denmark and recorded in the EUROCTO database. Major adverse cardio- and cerebrovascular events (MACCE) and admissions for cardiac symptoms were collected in the Western Denmark Heart Registry and through medical Journal Audits. Exposure was defined as successful revascularization of all CTO lesions compared to having one or more remaining CTOs after PCI attempt(s). Cost-effectiveness was evaluated as the net-benefit at patient level three years after treatment and through cost-effectiveness planes. Cost was defined as the cumulative cost of index procedure and admissions due to MACCE and cardiac symptoms. Effectiveness was defined as difference in MACCE for the primary analysis and difference in death and symptomatic admissions for the secondary. Results: Between 2009 and 2019, 441 patients with > 3 years of follow-up were treated with PCI for at least one CTO lesion (342 in the successful arm and 99 in unsuccessful arm). Technical success rate was 85.4%. In total 155 MACCE and 184 symptomatic admissions occurred in the follow-up period. Mean total cost was EUR 11.719 (11.034;12.406) in the successful group versus EUR 13.565 (11.899;15231) (p=0.02) in the unsuccessful group. Net-benefit was EUR 1.846 (64;3627) after successful revascularization for MACCE. Adjusted analysis found a NB of EUR 1481 (-118;3079). Bootstrap estimates showed cost-effectiveness planes in favour of successful revascularization. Conclusions: Patients fully revascularized for all CTO lesions had a more cost-efficient treatment. However, results need confirmation in a randomized controlled trial due to the risk of residual confounding after adjustment.